(untitled) (Architecture Image Studies, 2025)
For more than three centuries, the Teochew community has built a culturally vibrant and enduring presence in Vinh Chau, Soc Trang province. They have maintained their ancestral heritage while continuously adapting to the changing social environment. This study explores the core factors that influence their language choices, using rational choice theory to analyze how individuals and groups make decisions about language use. It also investigates the close relationship between language and culture, emphasizing how linguistic practices contribute to cultural transformation through acculturation. Drawing on qualitative research methods, the study includes in-depth interviews, detailed analysis of historical and contemporary documents, and a review of relevant academic literature. These approaches help uncover how the Teochew people manage their linguistic preferences in response to shifting cultural and social conditions. The research examines the role of government language policies, educational systems, and intercultural interactions in shaping patterns of language maintenance and change. By taking a multidimensional perspective, the article reveals both personal and collective motivations behind language behavior. It also raises important questions about the future of the Teochew language in the context of Vietnam’s modernization and increasing global integration. The findings offer meaningful insights into how language and cultural identity are deeply interconnected, and how linguistic decisions reflect and influence broader social realities.